(untitled) (International Journal of Social Sciences and Management, 2021)
The research focused on students who are pursuing their final year in three different professional courses- Master of Social Work, Bachelor of Education, and Bachelor of Nursing at three different educational institutions in Puducherry. This study adopted a descriptive research design and used interaction with a disable person (IDP) scale to understand the attitude of student professionals toward persons with disabilities and also to find what influences the attitude of future professionals. The primary aim is to learn more about the way students of three different professions generally view persons with disabilities and feel about interacting with this population. The interaction and attitude will create an impact on their practice of the profession in the future. The findings indicate that the students of three different professions were having a negative attitude towards PWDs but no significant difference was found in gender, locality, and course of study. Results also enlighten the educators, health professionals and non-governmental organizations to plan programs that shall create changes in the attitude of students towards PWDs. This research concludes with reflections on the need to revive the social interaction of student professionals with persons with disabilities. Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 306-311